ANALYSIS OF MATHEMATICAL COMMUNICATION ABILITY AND SELF REGULATED LEARNING MATHEMATICS STUDENT’S OF CLASS IX SMP NEGERI 2 CILAMAYA KULON - Fika Muji Fadhillah; Erna Hernawati (IKIP Siliwangi, 2019)
This study aims to determine mathematical communication ability and self-regulated learning mathematics of IX grade students of SMP Negeri 2 Cilamaya Kulon Karawang on circle material and circle tangents. This research is a qualitative descriptive study, where the object of research is class IX students as many as 35 students. This research was conducted on November 20, 2018. The research technique was in the form of a test of 6 items test questions of mathematical and non-test communication ability in the form of a questionnaire with 40 items of self regulated learning mathematical statements and interviews. The results of this study are mathematical communication ability of students classified as moderate with a reliability coefficient of 0.9793 (very high category), having a mean difficulty index of 0.539 (medium category), and a mean differentiation of 0.485 (good category). Student constraints when working on mathematical communication problems on circle material and tangent circle are students who are less able to analyze the core of the problem, students do not understand the form of non-routine questions (mathematical communication), students are confused in determining completion strategies, students cannot visualization, students do not know the terms in mathematics, as well as procedural errors in progress. While for self regulated mathematics students have a good category.